Comportamiento Epizootiológico de Parásitos Gastrointestinales en Caninos Domésticos (canis familiaris) en el sector Salache Sur de la Parroquia Eloy Alfaro del Cantón Latacunga. - Molina Mogro, Lissette Estefanía. (2018)
In the present investigation on "Epizootiological behavior of Gastrointestinal Parasites in domestic canines (canis familiaris) in the Sector of South Salache of the canton Latacunga had as objective the determination of the prevalence of gastrointestinal parasites in 150 domestic canines by means of the flotation technique. In the present investigation on "Epizootiological behavior of Gastrointestinal Parasites in domestic canines (canis familiaris) in the Sector of South Salache of the canton Latacunga had as objective the determination of the prevalence of gastrointestinal parasites in 150 domestic canines by means of the flotation technique. With the total of samples processed by the shaerth technique, the types of parasites were identified and the prevalence by parasitic group and by parasite genus was calculated, evaluating through the anamnesis the intrinsic factors: age, race, sex. The samples were taken from canines that had a stable home, were collected with the collaboration of the owners after identification of the individuals. To determine the parasitic load, the microscopic plate counting technique was used. It consisted in studying a microscopic plate that contains more or less 3mg of fecal matter quantity that was obtained approximately in the collection of the direct samples of the canine, later we carried out the preparation for the coprology. From the fecal samples of the domestic canines of the South Salache Sector, immediately analyzed in the laboratory, resulted in 92 cases as positive to parasitosis due to the loading of eggs present in the plates analyzed, representing 61.33% and 58 negative cases which represent 38.67% The result obtained from the samples taken gave us as results different types of gastrointestinal parasites which are the following: The 150 domestic canines analyzed have 63% positive cases of Ancylostoma caninum, 21% positive cases of Ascaris and 16% positive cases of Strongyloides. By means of the total analysis of the canines studied, we found that Ancylostoma caninum had the highest percentage of invaders with 63%.